The Influence of Entrepreneurship Education, Family Environment, and Entrepreneurial Motivation on Entrepreneurial Interest Among Students at Dian Nusantara University - Kurniawan, Anton; Tarmizi, Achmad (Sean Institute, 2025)
This study explores the influence of entrepreneurship education, family environment, and entrepreneurial motivation on the entrepreneurial interest of students at Dian Nusantara University. As the unemployment rate among university graduates continues to rise, entrepreneurship has emerged as a viable alternative to traditional employment. Using a quantitative approach, the study surveyed 70 students through structured questionnaires. Data were analyzed using validity and reliability tests, multiple linear regression, and classical assumption tests. The results show that entrepreneurship education, family environment, and entrepreneurial motivation each have a significant positive effect on students’ entrepreneurial interest, both individually and collectively. Notably, entrepreneurial motivation was found to be the most dominant factor. These findings highlight the need for universities to integrate more experiential entrepreneurship programs and for families to provide moral support. Ultimately, fostering entrepreneurial interest among students can contribute to the creation of self-sufficient graduates who are ready to innovate and generate employment.